Funding under borrowing limits in international portfolios - Tommaso Trani (Graduate Institute of International and Development Studies, 2012)
I develop an open economy portfolio model to study how leveraged investors' wholesale funding affects the international transmission of shocks. Under binding borrowing limits, there is a link between the international investment positions of integrated economies as investors diversify the asset side of their balance sheets. Building on this mechanism, I introduce the liability side, allowing investors sell domestic and foreign bonds and capturing changes in counterparty risk in a stylized way (i.e., debt-to-asset ratios are specific to each borrower and time-varying). I model and parameterize these ratios, conditional on portfolio choice. I can solve for portfolios taking advantage of the link between assets and liabilities which is implied by the borrowing constraints. Equilibrium portfolios feature home funding bias, which is justified by a crucial interaction between the terms of trade and the tightness of the borrowing constraints. Dynamically, this interaction implies that the source of debt which is most sensitive to shocks is foreign funding. In fact, any shock creates a wedge between the cost of funding in different countries; the value of collateral must adjust accordingly through asset prices. Yet, asset prices are mainly affected by financiers' concern for counterparty risk: impact effects are deep and in line with the terms of trade effect. Combined, these effects have somehow novel implications for the net foreign asset positions. The cumulative effects have instead more mixed results on fluctuations.
Keywords: E21; F32; F34; F41; G15; 330; borrowing limits; counterparty risk; financial flows; international financial markets; international; lending; macroeconomic interdependence; Portfolio-Management; Liquiditätsbeschränkung; Schock; Kapitalmobilität; Internationaler Finanzmarkt; Offene Volkswirtschaft; Theorie